"That's Not How the Story Ends:" Vincent Harding's Liberating Vision of African American Religious History. Issue 3 (2nd September 2019) - Floyd-Thomas, Juan M.
ABSTRACT: A critical reappraisal of Vincent Harding's transformative work as a preeminent historian of the African American freedom struggle is long overdue. Examining Harding's major works – There Is A River (1981), Martin Luther King: The Inconvenient Hero (1996), and Hope and History (1990) – this paper focuses on Harding's revisionist approach to US religious history by addressing three historiographical elements: radical reinterpretation of historical narrative from the perspective of the oppressed; the uses and abuses of biography in the historical representations of Dr. King in popular culture and collective memory; and articulation of a philosophy of history rooted in a theology of hope and human flourishing. This paper illustrates how Harding's writings advance a liberating vision for history as both a discipline and discursive realm in service to social justice and human dignity.